AESTHETIC EDUCATION AND PERCEPTION IN THE TEACHING OF LITERATURE OF FRATERNAL PEOPLES (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2025)
The article highlights a wide range of issues, such as the formation of students’ aesthetic attitudes, aesthetic views, artistic taste, analysis of the work, the formation of independent thinking in literature lessons.